Tonic and Phasic Nitric Oxide Signals in Hippocampal Long-Term Potentiation - Hopper, Rachel A. (J Neurosci, 2006)
Nitric oxide (NO) participates in long-term potentiation (LTP) and other forms of synaptic plasticity in many different brain areas but where it comes from and how it acts remain controversial. Using rat and mouse hippocampal slices, we tested the hypothesis that tonic and phasic NO signals are needed and that they derive from different NO synthase isoforms. NMDA increased NO production in a manner that was potently inhibited by three different neuronal NO synthase (nNOS) inhibitors. Tonic NO could be monitored after sensitizing guanylyl cyclase-coupled NO receptors, allowing the very low ambient NO concentrations to be detected by cGMP measurement. The levels were unaffected by inhibition of NMDA receptors, nNOS, or the inducible NO synthase (iNOS). iNOS was also undetectable in protein or activity assays. Tonic NO was susceptible to agents inhibiting endothelial NO synthase (eNOS) and was missing in eNOS knock-out mice. The eNOS knock-outs exhibited a deficiency in LTP resembling that seen in wild-types treated with a NO synthase inhibitor. LTP in the knock-outs could be fully restored by supplying a low level of NO exogenously. Inhibition of nNOS also caused a major loss of LTP, particularly of late-LTP. Again, exogenous NO could compensate, but higher concentrations were needed compared with those restoring LTP in the eNOS knock-outs. It is concluded that tonic and phasic NO signals are both required for hippocampal LTP and the two are generated, respectively, by eNOS and nNOS, the former in blood vessels and the latter in neurons.